The effect of hole shape on blade cooling effectiveness. (20th January 2011) - Yao, Yufeng; Yao, Jun
The high temperature conditions under which turbine blades operate pose a constraint on their service lifetime. One industrial solution is to apply the film cooling and the cooling effectiveness is generally determined by flow conditions, cooling hole geometry shapes and orientations. In this study, a total of four cooling hole geometries are considered as a cylindrical hole, a cylindrical hole with an upstream ramp, a shaped diffuser, and a double console slot. In all cases, the hole centreline has an inclination angle of 35 degrees against the mainstream airflow. Simulation starts with a base model of cylindrical hole and results have shown good agreement with available experimental data and numerical results. Using this configuration as a baseline, studies continued with three remaining geometries. It was found that for all three geometry variants the cooling effectiveness has considerable increase in comparison to that from the base model. The physical mechanism is primarily due to the weakening of the vortex structures in the vicinity of the hole exit, thus, reducing the penetration depth of the coolant jet flow and the entrainment of surrounding hot fluids.